"I really wanted her to have a Big Sister": Caregiver perspectives on mentoring for early adolescent girls. (May 2018) - Keller, Thomas E.; Overton, Bahia; Pryce, Julia M.; Barry, Johanna E.; Sutherland, Andrew; DuBois, David L.
Abstract: Formal youth mentoring programs tend to focus on the mentor-mentee dyad as the primary relationship cultivated and supported. The interests and preferences of the parent or caregiver in the mentoring relationship may receive little attention. In this study, semi-structured qualitative interviews were conducted with primary caregivers ( N  = 20) of early adolescent girls participating in a Big Brothers Big Sisters community-based mentoring program to explore reasons why they wanted mentors for their daughters. Thematic analysis revealed that caregivers expected mentors to support their daughters as trusted companions, confidants, and conduits to opportunities and services. In addition, caregivers noted ways in which mentoring offered them respite and reinforced their parenting. The findings highlight the potential value of assessing caregiver perspectives and priorities so that program staff and mentors can partner more effectively with youth and families for successful mentoring experiences. Highlights: Caregivers want mentors for their daughters to serve as companions and confidants. Caregivers want mentors for their daughters to act as conduits to opportunities and experiences. Caregivers benefit from the respite afforded by the mentoring relationship. Caregivers appreciate reinforcement of their parenting efforts by mentors.